Maquinitas y juegos chimbos : consumo de piratería de videojuegos y construcción de ciudadanía en Colombia (2017)
In Colombia the consumer experiences associated with the world of video games have been deeply linked to the piracy and the access possibilities that this favored. The pirated products and services have had a great influence on the development of the consumption practices of Colombian gamers, as well as in the imaginary that legitimized them. However, such practices are not approved by Colombian law and by many videogame developers, reflecting a set of tensions around redefining the rights and duties that gamers, as citizens, are subject to. Thus, the focus of the present work is to account for the relationship between consumption and citizenship construction through access to video game piracy, because it puts on the table what is socially relevant to certain sectors of civil society, as access to entertainment, as well as what is politically relevant to the State, such as the payment of taxes. The participants in this research were a group of video players from the city of Bogota who were born or raised in the nineties and early twenty-first century, and whose life histories account for the impact that technological changes, the design of the objects and the intensification of communications have had in the transformation of the desires and expectations of the new generations of the country, and, therefore, of their identities and ethical codes.--Tomado del Formato de Documento de Grado.